Time-Resolved Nanostructural Analysis of Catalyst Layer Formation Process by Synchrotron X-ray Scattering. (24th August 2017) - Konosu, Yuichi; Koga, Maito; Matsumoto, Hidetoshi; Tokita, Masatoshi; Masunaga, Hiroyasu; Hikima, Takaaki; Sugimori, Hidekazu; Yoshida, Toshihiko; Shinohara, Kazuhiko; Hirai, Shuichiro
Abstract : The film formation process of blade-coated catalyst ink was investigated by in-situ time-resolved grazing-incidence small-angle X-ray scattering (GISAXS) measurements utilizing synchrotron radiation. The GISAXS profiles were measured as a function of the time elapsed after coating the ink, t . As increasing t, the peak at around q z ~ 0.2 nm −1 shifted toward smaller q z . At t ~ 50 s, two peaks appeared at around q z ~ 0.5 nm −1 and then combined into one peak. These peak shifts would be ascribed to Pt/C agglomeration induced by solvent evaporation.